Mediation effect of knowledge management on the impact of IT capability on firm performance: exploring the moderating role of organization culture management - Wu, Weiwei; Li, Xue; Surangkana, Bowornsintuchon (Frontiers in Psychology, 2024)
We try to find out how the mediator and moderator in information technology capability affects firm performance. In this study, we employed knowledge stock and knowledge process as mediators and organizational culture management as moderators. The results showed that information technology capability has a directly positive effect on firm performance and indirectly impact on firm performance via knowledge stock and knowledge process. Moreover, organizational culture management moderates the relationship between knowledge stock/ process, and firm performance.